Explaining the Failure in Agricultural production in subSaharan Africa - Nkamleu, G.B.; Gockowski, J.; Kazianga, H. (2003)
This paper examines changes in agricultural productivity in 10 Subsaharan countries. The relative performance of agricultural sector was gauged using data envelopment analysis. From a panel data set of the 10 countries which included the 28-year period 1972-1999, mathematical programming methods were used to measure Malmquist indexes of total factor productivity. It was found that, during that period, total factor productivity have experienced a negative evolution in sample countries. A decomposition of those measures suggest that, most of the weak performance of factors productivity is attributable more to technological change than technical efficiency change. French-speaking countries better succeeded to raise their productivity than English-speaking countries do. In addition, it have been found that Sahelian countries failed to rise their agricultural productivity compared to forest countries where a positive evolution have been detected.